Current legal issues: The phenomenon of social rights in the constitutional law in the countries of Central and Eastern Europe - Melnikov, Victor Yu.; Valeriya A. Danilova, Anna V. Aleksandrova, Alena L. Guseva,; Seregin, Andrei V. (Opción, 1970)
The study includes an assessment of the effectiveness of state regulation of public relations in the countries of Central and Eastern Europe (CEE). The authors proceed from the traditional interpretation of social rights as a set of individual rights in the sphere of labor, social security, medical care, education, etc. The Phenomenon of social rights is studied by historical and comparative methods. Nevertheless, it was the socialist constitutions that put social rights at the top of the list of individual rights and reinforced them with a wide range of guarantees that allowed them to be realized. After the "velvet revolutions" of the late twentieth century, many CEE countries tried to preserve social rights in their new constitutions.